Upaya Meningkatkan Kepercayaan Pada Organisasi Melalui Perbaikan Perilaku Pemimpin dan Keadilan Organisasi - Patras, Yuyun Elizabeth; Hidayat, Rais (Universitas Negeri Surabaya, 2018)
Organizational trust is essential so that members of the organization can continue to contribute to the progress of the organization. The purpose of this research is to find out how far the variables of leadership behavior and organizational justice on improving organizational trust. The research method used is associative quantitative causal method, and the testing hypothesis research using path analysis technique. The population in this study is 707 permanent lecturers who have the National Lecturer Number (NIDN). The sample is 130 respondents. The instrument test was conducted to 30 respondents outside the sample. The findings of this research indicate that the higher the leadership behavior in directing subordinates, providing support to subordinates; increase member participation in achieving organizational goals, and rewarding the achievers, the higher the trust in the organization. Other findings show that the higher the organization's justice the higher the trust in the organization.